Pendidikan Kesehatan Tentang Keputihan dengan Menggunakan Rebusan Daun Sirih pada Remaja - Muslimah Muslimah; Yayuk Eliyana (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Vaginal discharge or flour albus is an excessive discharge from the vagina that is not menstrual blood. Pathological fluoride albus caused by vaginal infections (fungi, bacteria, parasites, viruses). The prevalence of causes is 25%-50 candidiasis, 20%-40% bacterial vaginosis and 5%-15% trichomoniasis. The characteristics of pathological vaginal discharge are smelly, itchy, yellowish or greenish, thick and cloudy and large in quantity. If this condition does not receive immediate treatment, it will have a negative impact on women's health. Infection will develop and affect the function of the reproductive organs. Medical treatment efforts include administering drugs in the form of capsules, tablets and ovules (vaginal tablets). Meanwhile, for non-medical or complementary therapy, betel leaf decoction can be used (Dame, 2023). The aim of this outreach is to provide education about the benefits of boiled betel leaves for vaginal discharge in women of childbearing age. The activity was carried out at the Nyalabu Daya Pamekasan village hall in July 2024, the subject was women of childbearing age in at the Nyalabu Daya Pamekasan village hall. Activity results: Counseling participants learned about the benefits of boiled betel leaf water for vaginal discharge. The results of the questionnaire measuring knowledge before and after counseling showed an increase in knowledge of women of childbearing age by an average of 94%. It is hoped that women of childbearing age can maintain personal hygiene to prevent vaginal discharge and can use boiled water from betel leaves to treat vaginal discharge that occurs.